Migration mechanism and risk assessment of chlorinated paraffins in highly polluted Ya'Er lake area, China. (15th July 2021) - Li, Chang; Chen, Lufeng; He, Yujian; Liang, Yong; Wang, Yingjun; Li, Feifei; Gao, Wei; Wang, Yawei; Jiang, Guibin
Abstract: Chlorinated paraffins (CPs), a type of toxic and persistent organic substances, can persist in environmental media for a long time and have adverse effects on human health. Thus, it is of great importance to investigate the accumulation and environmental behavior of CPs in industrial areas. In this study, farmland soil, water, and sediment core samples from abandoned oxidation ponds used by three chemical plants to treat wastewater over the past 38 years were investigated in detail. Results show that the concentration of CPs in sediments varied significantly with the water flow direction. The oxidation pond closest to a sewage outlet had the highest concentrations of short-chain chlorinated paraffin (SCCPs) and medium-chain chlorinated paraffin (MCCPs), within the ranges of 44.0–6.21 × 10 4 ng/g dw (mean 9.32 × 10 3 ng/g dw) and 143–1.30 × 10 6 ng/g dw (mean 1.22 × 10 5 ng/g dw), respectively. However, in the oxidation pond farthest from the sewage outlet, CP concentrations in sediments were significantly reduced, with ∑SCCPs and ∑MCCPs concentrations ranging from N.D.-249 ng/g dw (mean 66.8 ng/g dw) and N.D.-222 ng/g dw (mean 34.0 ng/g dw), respectively. Moreover, MCCP level in the water was below the detection limit, while the concentration of SCCP ranged from 41.0 to 1.53 × 10 3 ng/L (mean 267 ng/L). Finally, a remarkable spatial trend and specific congener distribution were observed in the sediment test results. The horizontal and vertical distributions of the sediments indicate that short-chain (C10-11 ) and low-chlorinated (Cl6-7 ) homologs are more likely to migrate deeper or farther away from the pollution source. Graphical abstract: Image 1 Highlights: The CPs concentration was the highest near the pollution source, which came from historical accumulation. The CPs concentration decreased with the water flow direction. The lighter CPs (C10-11, Cl6-7 ) in sediment are more likely to migrate farther/deeper from pollution sources. The concentration level of CPs in the study area may cause health risks to humans. Abstract : CP homologs with shorter carbon chains (C10-11 ) and fewer chlorine atoms (Cl6-7 ) are more likely to migrate away from the pollution source.